Assessment of atherosclerosis and endothelial dysfunction risk factors in patients with primary glomerulonephritis - Hagemann, Rodrigo [UNESP] (2023)
Universidade Estadual Paulista Júlio de Mesquita Filho, Faculdade de Medicina de Botucatu